The Obligation to Provide Tax Audit Results to Taxpayers in Tax Disputes: An Educational Perspective on Transparency, Accountability, and Tax Literacy - Kalam Al Iqbal; Christian Andersen (Journal of Social Science and Humanities, 2025)
Tax disputes arise from disagreements between taxpayers and tax authorities, typically due to differing interpretations of tax regulations or audit procedures. One recurring issue concerns the obligation to deliver the Audit Report (Laporan Hasil Pemeriksaan/LHP) to taxpayers prior to the issuance of a tax assessment letter. This study aims to examine the legal obligation to provide the audit report from the perspective of legal certainty and the principle of checks and balances in tax dispute resolution. The research employs a normative-empirical method using a case study approach of Tax Court Decision Number PUT-011120.99/2023/PP/M.XIIB/Tahun 2024. The normative analysis reviews the provisions of the Law on General Provisions and Tax Procedures (UU KUP) and its implementing regulations, while the empirical analysis evaluates the legal reasoning of the panel of judges in the decision. The findings indicate the existence of legal uncertainty regarding the obligation to deliver the audit report, which in practice may reduce transparency and weaken the protection of taxpayers’ rights. Although the panel held that the Tax Assessment Letter was legally valid because a Notification of Audit Findings (SPHP) had been issued, the decision did not comprehensively address the obligation to provide the audit report under applicable legislation. Therefore, regulatory clarification is necessary to ensure legal certainty and to maintain a balanced relationship between tax authorities and taxpayers.